KARAKTERISASI FILM PVA/KITOSAN/ZEOLIT TERSUBTITUSI ION Ag+ BERPOTENSI SEBAGAI KEMASAN AKTIF - Dina Kartika Maharani; Rizka Dwi Safitri (Unesa Journal of Chemistry, 2022)
The need for fresh food continues to increase. Fresh food has a short shelf life. This can be overcome by active packaging containing antimicrobial substances. Zeolite is modified by ion exchange with silver, where silver acts as an antimicrobial agent. This study aims to study the changes in the mechanical properties of the PVA/chitosan mixture with the addition of zeolite-Ag compared to without the addition of zeolite-Ag. The variation in this study is the addition of zeolite-Ag to the PVA/CS composite, namely (0.025; 0.05; 0.1; 0.2)%. The films that have been made were analyzed in terms of mechanical properties, FTIR, and surface morphology microstructure. Composite films containing zeolite-Ag showed an increase in tensile strength and elasticity, where confirmed zeolite can be used as a reinforcing material in polymer matrices. The composite film with 0.025% zeolite-Ag content has a tensile strength value of 46.534 MPa, because zeolite-Ag can be homogeneously dispersed in the polymer matrix. FTIR analysis showed that the mixture of PVA and chitosan proved to be uniformly mixed. Morphological microstructural analysis showed homogeneous surface results, there was no visible appearance of zeolite-Ag aggregates on the PVA/CS film, whereas on films containing 0.025% zeolite-Ag there was a heterogeneous surface and the appearance of black circles indicating the presence of zeolite-Ag. Key words: characterization, film composite, zeolit, silver